2016
DOI: 10.1080/08856257.2016.1141509
|View full text |Cite
|
Sign up to set email alerts
|

Modelling inclusive special needs education: insights from Dutch secondary schools

Abstract: Dam c a the nHl/Ecno polytechnic of Groningen, Groningen, the netherlands; b faculty of Social and Behavioural Sciences, university of amsterdam, netherlands academy of leadership in Education, amsterdam, the netherlands; c faculty of Social and Behavioural Sciences, university of amsterdam, research institute of child development and Education, amsterdam, the netherlands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…Whereas, other aspects received the moderate level of needs. Studies have shown that management of inclusive education is important which involves the collaboration process to support the inclusive school [25][26][27]…”
Section: The Results Of Analysis On the Level Of Needs On The Inclusivmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, other aspects received the moderate level of needs. Studies have shown that management of inclusive education is important which involves the collaboration process to support the inclusive school [25][26][27]…”
Section: The Results Of Analysis On the Level Of Needs On The Inclusivmentioning
confidence: 99%
“…Quality assurance is done by modifying the curriculum, administrative organization, and appropriate pedagogical strategies. Collaboration is very supportive in the management of inclusive education [25][26][27]. Consistent support and services are provided, according to the special needs of inclusive students.…”
Section: Inclusive Education Modelthe Whole School Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A temática de educação inclusiva tornou-se uma espécie de "Agenda Global" (RUNSWICK-COLE, 2011) e é um dos campos mais explorados em pesquisas educacionais. Na declaração de Salamanca em 1994, os países signatários assumiram o compromisso de promover políticas que garantam o acesso a todos, em idade escolar, na instituição de ensino comum mais próxima de sua residência (RUNSWICK-COLE, 2011;VAN DER BIJ et al, 2016). Este compromisso contrapõe à prática de educação segregada na qual os estudantes com deficiência são matriculados em escolas especializadas que atendem somente este público (VAN DER BIJ et al, 2016).…”
Section: Introductionunclassified
“…Gaining from the global experience (Van der Bij, Geijsel, Garst, Ten Dam, 2016;Emam, 2016;Futaba, 2017;Carrington, Pillay, Tones, 2017;Suc, Bukovec, Karpljuk, 2017) and already available Russian experience (Alekhina, 2016;Karpushkina, 2017;Osmuk, Degtyaryova, Zhdanova, 2017), inclusive education may and should become this kind of education. It is inclusive education that is such kind of organization of the education process, in which all children, regardless of their physical, psychic, intellectual, cultural and ethnical, language and other special features, are included in the general comprehensive education system and are educated next to the place of their living together with their peers without any disability in the same general comprehensive education school, where their special education needs are be taken into consideration and such children are given special care and support.…”
Section: Introductionmentioning
confidence: 99%